If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(6x + 3) = 84 Reorder the terms: 4(3 + 6x) = 84 (3 * 4 + 6x * 4) = 84 (12 + 24x) = 84 Solving 12 + 24x = 84 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 24x = 84 + -12 Combine like terms: 12 + -12 = 0 0 + 24x = 84 + -12 24x = 84 + -12 Combine like terms: 84 + -12 = 72 24x = 72 Divide each side by '24'. x = 3 Simplifying x = 3
| 4x+4-2x=2x-2x+6 | | 10x^2+37x+3=-4 | | 8+3=6x-9 | | 3x=-24x+33 | | -6x=-3(2x+4) | | 7-2x=10+4c | | 180=m+80 | | (1+y)(2y+5)=0 | | y=-4x^2+36x | | 2(9+3x)=36 | | A=21x+kx | | -6(3+x)=-48 | | 5(7+3x)=140 | | 5x-4(2x-11)=29 | | 2(1+6x)=-10 | | 2/3=10/n | | 1+5x+4x=82 | | 9x/4/10= | | 3(7+4x)=69 | | 3(2x-4)=6x+12 | | 26x+5=7x+10 | | 27x-18=20 | | ln(2x+7)=6 | | y/7=2/3-1/5 | | 5x+4+4x=103 | | 75=35+8x | | -3(7x+9)=-132 | | V/9=-3.7 | | 12x^2+23x+30=0 | | 9x4/10 | | 2x+10+7x=10 | | 7/8(x-1/2)=-49/8 |